From consultors to collaborators – An SOP for advancing ethics engagement in science - Varsha Aravind Paleri; Kristien Hens (Synthetic and Systems Biotechnology)
Synthetic Biology (SynBio) is an interdisciplinary field that tackles global challenges in healthcare, sustainability, food production, among others. However, it also presents critical ethical concerns, including biosecurity, justice, and the unintended consequences of research biases. Addressing these concerns requires timely and systematic ethical evaluation. Conventional approaches often relegate ethics to an external, procedural role rather than embedding it within the core of scientific inquiry, leading to delayed engagement and associated challenges. This article introduces a structured, stage-wise Standard Operating Procedure (SOP) to support the systematic integration of ethics into scientific research. Particularly beneficial for early-career researchers and ethicists, this framework offers a practical method for incorporating ethical reflection throughout the research process.